DEVELOPMENT, CREATION, PRODUCTION AND IMPLEMENTATION OF COLLECTION MODELS OF A MODERN DOMESTIC PASSENGER CARS FOR THE HIGH-SPEED TRANSPORT - Fediushyn, Yu. M.; Loboiko, L. M.; Pshinko, O. M.; Myamlin, S. V.; Donchenko, A. V.; Prykhodko, V. I.; Shkabrov, O. A.; Ihnatov, H. S.; Vysokolian, M. V.; Makarenko, V. M. (Science and Transport Progress, 2005)
In article the basic stages of creation, development of production and introduction of family of high-speed carriages on Open Society «КВСЗ» together with the leading scientific organizations are opened.